Geometria para alunos surdos por meio do tangram - GEMAQUE, Rafaela Maria Lucena (2020)
The present paper treats the investigation about how the deaf students understands the geometric content in the basic education, by that way the research objective intends to verify if the deaf students, by using ludic activities in basic geometrics, present evidences that are indications of involvement and learning. The research addresses as theoretical reference the side in the education of deaf people of the ludic and of the mathematical education, in which we look guiding elements to restrict to the thematic of this study. By that mean, the study was developed in a specialized teaching unit for the deaf people, located in an easy access district of the city of Belém, Pará, with three deaf students of the first stage class of the Young and Adults Education program. The data of the research were collected during the time of five weeks, between the months of September and October. The strategies used were the following: observations in class and register of the activities realized with the students, by filming. With the analyze of the research data we noticed that the results were achieved, because the students were capable of understanding the content of basic geometrics associated to the didactic resource used and they had developed the process of interaction one with another. By the end of this research we concluded that the developed practices by teachers in classroom, by using visual resources and concrete materials can opportune creativity, the interactivity, and teaching and learning to the deaf students.